Criticism Not Always Make You Angry: The Effect of Criticism and Sensitivity to Criticism Toward Anger - Jaro'ah, Siti; Deliana, Sri Maryati; Martiarini, Nuke (Developmental and Clinical Psychology, 2023)
Emotion is a psychological aspect that influences people's actions and behaviors. Anger is one of the negative emotions that can arise due to various factors, including criticism. Individuals have a different threshold for criticism called sensitivity to criticism. This study aims to examine the effect of giving criticism on one's anger and the impact of sensitivity to criticism to participants’ level of anger. This research used a mixed-method approach through experimental methods, interviews, and observations. The experiment research design used was a pre-test post-test control group design. The participants involved 15 undergraduates allocated into experimental group (8 participants) and control group (7 participants). The instruments used to measure anger was the adaptation of STAXI developed by Spielberger, and the sensitivity to criticism scale was used to measure sensitivity to criticism. The results showed no effect of giving criticism on increasing anger in the experimental group. In addition, Pearson correlation results between sensitivity to criticism and anger showed no impact of sensitivity to criticism on their anger. However, the interview noticed that participants experienced anxiety, anger, and fear. Instead of not feeling anger, the subject tried to hold back the feelings of anger and had similar experiences so that the criticism given had no effect. Similar to the interview result, we observed that participants showed multiple signs of anxiety such as fiddling their fingers and toes or showing a worried look.